REPRESENTASI PESAN MORAL DALAM FILM TILIK (ANALISIS SEMIOTIK ROLAND BARTHES) - Intan Leliana; Mirza Ronda; Hayu Lusianawati (Universitas Bina Sarana Informatika, 2021)
Recent films have attracted a lot of audiences, because many films have appeared with moral messages. This is evidenced by the number of films circulating by instilling the value of positive messages that are packaged in a concise, straightforward and interesting manner. So that many film makers have emerged to produce their works so that they can be watched by the public and can have a positive impact. Of the many films that are presented on the big screen, they have offered various colors in such a way, of course, adapted to the phenomena that are happening in society. Among them are the variety of films that are presented on the big screen, some are moral messages that are so constructive and in accordance with actual events in society, one of which is the short film “Tilik”. The research method used is qualitative in the form of semiotic analysis of Tilik Film Representations, this approach also allows researchers to use data as well as possible to be able to develop components of analytical, conceptual, categorical and flexible information. There are many signs in Tilik Film which have implied meanings. Director Tilik is very good at wrapping moral messages through the daily life of the village community through a film that only lasts 32 minutes, 34 seconds. These signs are displayed through several aspects such as the setting and setting of the film, shooting techniques, characters and dialogue between characters, scenes made by players, to the selection of the wardrobe of the characters in the film Tilik. These aspects then help build the film's storyline that produces moral messages. Keywords: representation, roland barthes semiotics, film